Pilot study for compact microbeam radiation therapy using a carbon nanotube field emission micro‐CT scanner. Issue 6 (15th May 2014) - Hadsell, Mike; Cao, Guohua; Zhang, Jian; Burk, Laurel; Schreiber, Torsten; Schreiber, Eric; Chang, Sha; Lu, Jianping; Zhou, Otto
Abstract : Purpose: Microbeam radiation therapy (MRT) is defined as the use of parallel, microplanar x‐ray beams with an energy spectrum between 50 and 300 keV for cancer treatment and brain radiosurgery. Up until now, the possibilities of MRT have mainly been studied using synchrotron sources due to their high flux (100s Gy/s) and approximately parallel x‐ray paths. The authors have proposed a compact x‐ray based MRT system capable of delivering MRT dose distributions at a high dose rate. This system would employ carbon nanotube (CNT) field emission technology to create an x‐ray source array that surrounds the target of irradiation. Using such a geometry, multiple collimators would shape the irradiation from this array into multiple microbeams that would then overlap or interlace in the target region. This pilot study demonstrates the feasibility of attaining a high dose rate and parallel microbeam beams using such a system. Methods: The microbeam dose distribution was generated by our CNT micro‐CT scanner (100 μ m focal spot) and a custom‐made microbeam collimator. An alignment assembly was fabricated and attached to the scanner in order to collimate and superimpose beams coming from different gantry positions. The MRT dose distribution was measured using two orthogonal radiochromic films embedded inside a cylindrical phantom. This target was irradiated with microbeams incident from 44 different gantry angles to simulate an array of x‐ray sources as in the proposed compact CNT‐based MRT system. Finally, phantom translation in a direction perpendicular to the microplanar beams was used to simulate the use of multiple parallel microbeams. Results: Microbeams delivered from 44 gantry angles were superimposed to form a single microbeam dose distribution in the phantom with a FWHM of 300 μ m (calculated value was 290 μ m). Also, during the multiple beam simulation, a peak to valley dose ratio of ∼10 was found when the phantom translation distance was roughly 4x the beam width. The first prototype CNT‐based x‐ray tube dedicated to the development of compact MRT technology development was proposed and planned based on the preliminary experimental results presented here and the previous corresponding Monte Carlo simulations. Conclusions: The authors have demonstrated the feasibility of creating microbeam dose distributions at a high dose rate using a proposed compact MRT system. The flexibility of CNT field emission x‐ray sources could possibly bring compact and low cost MRT devices to the larger research community and assist in the translational research of this promising new approach to radiation therapy.